P008: Care of palliative patients by paramedics in the 911 system. (May 2020) - Wallner, C.; Welsford, M.; Lutz-Graul, K.; Winter, K.
Abstract : Introduction: Palliative Care aims to relieve suffering and improve the quality of living and dying in patients with life-limiting, progressive conditions. Many patients and families prefer to stay at home at end of life. Despite this, many access 911 in times of apparent crisis. It has been noted in the literature that a well functioning palliative care system includes considering Emergency Medical Services as part of the patients' circle of care. Training in palliative care is traditionally limited or absent for prehospital clinicians, including Paramedics and Emergency Medical Services Physicians. Furthermore, in our region, there are currently no medical directives available to Paramedics within the 911 system specifically addressing the needs of palliative care patients. Methods: A feasibility study (Expanding Care by Paramedics for Palliative Patients – EC3P) was designed to evaluate implementation of a new palliative care medical directive with trained teams of Paramedics available to respond to 911 calls. As part of this study, a pre-implementation retrospective chart review was performed. Patient care records were screened for "palliative" within the past medical history and text fields. Information about dispatch and scene times, patient demographics, details of patient encounter, and disposition of the patient were recorded. Descriptive statics were used. Results: Data was reviewed for all calls in 2018. Call data was reviewed to exclude those that were pediatric (<18yo) and those whose palliative status was unknown or unclear. There was a total of 318 calls. The majority of the calls (83%) were between 7am and 8pm, with peaks at 10 am and 6pm. The majority were transported to hospital (74%), 16% were transferred to hospital initiated by their palliative care physician, 20% "refused" transport, and 6% were declared dead and not transported. The most common reasons for calling 911 were new symptoms or a sudden worsening of chronic symptoms, followed by needs exceeding caregiver capacity; the third most common was lift assist without apparent injury. Conclusion: Much is unknown about the palliative patient population as it intersects with prehospital emergency care. This study will help provide information needed to guide further research and implementation.